Fusion of SAR and optical images for earth remote sensing - Liu, Shurui (2015)
In this paper, I introduced the image fusion method of optical and SAR images of Earth remote sensing based on RGB-IHS transform. In the experiment, I first performed the image registration and image smoothing on the image. Also, I analyzed the effect of image smoothing with mean filter and median filter. Then, I performed RGB-IHS transform with direct method, weighted average method and high pass filter method for the image fusion. The fusion results show that the direct method may cause serious color distortion and low spatial resolution. The weighted average method with proper weighting average factor can give better fusion result with good spatial texture characteristic, spatial resolution and color information. While high pass filter method with Butterworth filter and proper weighting average factor can further improve the fusion quality.